2018
DOI: 10.1016/j.comppsych.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Reduced willingness to invest effort in schizophrenia with high negative symptoms regardless of reward stimulus presentation and reward value

Abstract: Background: Negative symptoms in schizophrenia, which are related to poor functioning, are thought to be grounded on aberrant functioning in the reward system. We aimed to disentangle how negative symptoms and two cognitive aspects of goal-directed behavior, mental representation of reward and reward value, affect willingness to invest effort to attain a reward in schizophrenia. Aims and procedures: To this purpose, 43 schizophrenia patients and 35 healthy controls were assessed for negative symptoms and gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 49 publications
2
19
1
Order By: Relevance
“…Amotivation and effort-related impairments are common symptoms in many mental disorders, including schizophrenia (Fervaha et al, 2015) and depression (Clery-Melin et al, 2011). Both are associated with a lack of goal-directed behavior, impeding daily functioning (Barch et al, 2014;Bergé et al, 2018). However, effort-related impairments are sensitive to the tasks in question (Horan et al, 2015;Reddy et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amotivation and effort-related impairments are common symptoms in many mental disorders, including schizophrenia (Fervaha et al, 2015) and depression (Clery-Melin et al, 2011). Both are associated with a lack of goal-directed behavior, impeding daily functioning (Barch et al, 2014;Bergé et al, 2018). However, effort-related impairments are sensitive to the tasks in question (Horan et al, 2015;Reddy et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Others have linked negative and depressive symptoms, both prevalent in schizophrenia ( an der Heiden et al, 2016 ) to amotivation ( Pelizza and Ferrari, 2009 ), and accordingly to a lack of goal-directed behavior ( Brown and Pluck, 2000 ). A range of studies have found that individuals with psychotic disorders or schizophrenia have effort-related impairments ( Barch et al, 2014 ; Whitton et al, 2015 ) and that there is an association between the degree of negative symptoms and these impairments ( Bergé et al, 2018 ). In healthy populations similar findings have been reported for negative symptom-like phenomena ( Stefanis et al, 2002 ; Terenzi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of our variables of interest correlated with negative symptom severity. This may seem unexpected, as previous studies have demonstrated a negative relationship between negative symptom severity and effort investment (e.g., Gorissen et al, 2005;Wolf et al, 2014) or that effort investment was predominantly impaired in subgroups scoring high on negative symptoms (Granholm et al, 2006;Bergé et al, 2018). However, other findings indicate that the relationship between effort investment and negative symptoms may, in fact, be non-linear and moderated by other factors, such as defeatist attitudes (Granholm et al, 2016;Reddy et al, 2018).…”
Section: Discussionmentioning
confidence: 78%
“…Working memory deficits are commonly reported in persons with schizophrenia (SCZ; e.g., Horan et al, 2008 ; Ventura et al, 2009 ; Freeman et al, 2014 ) and have been explained by a lack of processing resources ( Nuechterlein and Dawson, 1984 ; Granholm et al, 1997 ). However, persons with SCZ, particularly when negative symptoms are prevalent, seem to be less willing to engage with physically ( Gold et al, 2013 ; Barch et al, 2014 ; Bergé et al, 2018 ) or cognitively effortful tasks ( Wolf et al, 2014 ; Gold et al, 2015 ; Culbreth et al, 2016 ; Reddy et al, 2018 ; Chang et al, 2019 ) and, when engaged, tend to exert less effort during task performance ( Gorissen et al, 2005 ; Granholm et al, 2006 , 2016 ). Accordingly, diminished performance on cognitive tests of persons with SCZ might be explained not only by real cognitive impairments or limited resources but also by reduced invested effort ( Gorissen et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%